Product management in the digital era: Theory and practice - Pingali, Srinivas R.; Prakash, Shankar; Korem, Jyothi R.; Pedada, Kiran (London Routledge, 2025)
Consumer and industrial products have evolved significantly over the last century, from physical to virtual products, services, and hybrid products. Product management has had to change and adapt to the rapidly changing business environments. This textbook offers an in-depth look into the role, what the job entails, and what skills it requires. Product managers are required to manage the ideation, development, production, marketing, and distribution of a product.